Acute Hypomagnesemia-Induced Cerebellar Down-Beat Nystagmus Syndrome Due to Benign Paroxysmal Positional Vertigo: A Case Report - Marcelli, Vincenzo; Giannoni, Beatrice; Marcelli, Edoardo; Volpe, Giampiero; Faralli, Mario; Rita Fetoni, Anna; Enrico Pettorossi, Vito (Journal of Neurological Research And Therapy, 2024)
Magnesium is essential for the proper functioning of all human cells and is involved in the regulation of neurotransmitter function and neurological function. Acute and chronic hypomagnesemia cause severe neurological symptoms such as neuromuscular irritability, myoclonus, stridor, dysphagia, mainly postural tremor and movement disorders along with vertical downbeat nystagmus. Here we report a case of cerebellar downbeat nystagmus syndrome induced by acute hypomagnesemia (HICS) due to very frequent vomiting in a 75-year-old woman with benign paroxysmal positional vertigo (BPPV). The clinical condition improved with daily intravenous and then oral magnesium supplementation. To our knowledge, this is the first described case of HICS induced by acute hypomagnesemia due to vomiting triggered by a benign peripheral pathology such as BPPV which was then successfully treated once the central syndrome was resolved.
Keywords: Benign paroxysmal positional vertigo (BPPV); vomiting; hypomagnesemia; down beat nystagmus (DBN); down beat nystagmus syndrome (DBNS)